The Impact of Practicing Sports Activities on Reducing University Violence from the Point of View of Students of the Faculty of Sports Science at Mutah University - Prof. "Zainalabedin" Mohammad Bani Hani; Dr. Sofyan M. Alleimon (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Student violence is a fundamental issue that the university administration must handle. Many pupils who lack mental fortitude participate in violent activities. This study explores, from a student's perspective, how athletic activity influences the level of violence on college campuses. This study's sample consists of students from the department of physical education at Mutah University. 600 students from Mutah University's faculty of physical education participated in the survey. In the sample, there were 324 male and 276 female students. According to the research findings, student participation in sports activities plays a significant effect in preventing violence. The study recommended developing standards and procedures to encourage university students to participate in athletics. This research has produced an important framework that is also an original contribution to knowledge. In addition, the research has credible theoretical implications that contribute to expanding the body of knowledge. Similarly, the practical consequences of this study are reliable for enhancing university students' participation in sports activities. This study has several limitations discussed in conjunction with its future directions.